Morphological and molecular analysis of apoptosis in the corpus cavernosum of rats submitted to a chronic alcoholism model1 - Meirelles, Rogério José de Azevedo; Neto, Fermino Sanches Lizarte; Cirino, Mucio Luiz de Assis; Novais, Paulo Cezar; Gula, Isabella Stracieri; Silva, Jairo Pinheiro da; Tazzima, Maria de Fátima Galli Sorita; Fazan, Valéria Paula Sassoli; Durand, Marina Toledo; Tirapelli, Daniela Pretti da Cunha [UNESP]; de Carvalho, Camila Albuquerque Melo; Schimming, Bruno César [UNESP]; et al. (FapUNIFESP (SciELO), 2020)
Purpose: To evaluate the effect of chronic alcoholism on morphometry and apoptosis mechanism and correlate with miRNA-21 expression in the corpus cavernosum of rats. Methods: Twenty-four rats were divided into two experimental groups: Control (C) and Alcoholic group (A). After two weeks of an adaptive phase, rats from group A received only ethanol solution (20%) during 7 weeks. The morphometric and caspase-3 immunohistochemistry analysis were performed in the corpus cavernosum. The miRNA-21 expression was analyzed in blood and cavernous tissue. Results: Chronic ethanol consumption decreased cavernosal smooth muscle area of alcoholic rats. The protein expression of caspase 3 in the corpus cavernosum was higher in A compared to the C group. There was no difference in the expression of miRNA-21 in serum and cavernous tissue between the groups. Conclusion: Chronic ethanol consumption reduced smooth muscle area and increased caspase 3 in the corpus cavernosum of rats, without altered serum and cavernosal miR-21 gene expression.
Keywords: Apoptosis; Erectile Dysfunction; Ethanol; MicroRNAs; Rats